Phase angle and extracellular water-to-total body water ratio estimated by bioelectrical impedance analysis are associated with levels of hemoglobin and hematocrit in patients with diabetes. Issue 4 (April 2023) - Hori, Taiki; Nakamura, Shingen; Yamagami, Hiroki; Yasui, Saya; Hosoki, Minae; Hara, Tomoyo; Mitsui, Yukari; Masuda, Shiho; Kurahashi, Kiyoe; Yoshida, Sumiko; Harada, Takeshi; Kuroda, Akio; et al.
Abstract: Background: Anemia is one of the common complications of diabetes and is associated with mortality. Phase angle (PhA), ratio of extracellular water to total body water (ECW/TBW) and skeletal muscle mass index (SMI) estimated by bioelectrical impedance analysis (BIA) have been used as prognostic indicators for various chronic diseases and frailty. We aimed to clarify the clinical significance of PhA, ECW/TBW and SMI for anemia in patients with diabetes. Materials and methods: The values of PhA, ECW/TBW and SMI were estimated by a portable BIA device and blood samples were collected in 371 Japanese patients with diabetes. The relationships of PhA, ECW/TBW and SMI with hemoglobin (Hgb) and hematocrit (Hct) were statistically evaluated. Results: In simple linear regression analysis, PhA and SMI were positively correlated with Hgb and Hct levels in total subjects, male subjects and female subjects. In contrast, ECW/TBW was negatively correlated with Hgb and Hct levels regardless of sex. Multivariate regression analysis showed that both PhA and ECW/TBW but not SMI independently contributed to Hgb and Hct levels after adjustment of clinical confounding factors in both males and females. Conclusions: PhA and ECW/TBW but not SMI were associated with levels of Hgb and Hct in patients with diabetes. Therefore, aberrant values of PhA and ECW/TBW suggest a risk of anemia in diabetic patients.